INDICATORS OF TOTAL IMMUNOGLOBULINS IN PATIENTS WITH ARTHROTIC ARTHRITIS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The work included a comprehensive laboratory examination of patients with different stages of knee osteoarthritis. The patterns of metabolic disorders in patients with osteoarthritis in the form of activation of the prooxidant system and inhibition of the enzymatic link of antioxidant protection were revealed. It was shown that the degree of oxidative stress clearly correlates with the severity of clinical manifestations of osteoarthritis. The most clinically significant blood parameters for laboratory diagnostics of this pathology were identified, such as aliphatic aldehyde groups of oxidized proteins and paraoxanase activity.